Archaeological expedition to al khashbah (2023): Ibra south - Schmidt, Conrad; Kluge, Jonas; Biezeveld, Irini (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
A small, newly discovered Umm an-Nar settlement close to the southern outskirts of the modern city of Ibra was investigated by a team from the University of Frankfurt, Germany between 1 March 2023 and 11 April 2023. The investigation included a detailed surface survey with find collection, as well as small-scale excavations at two of the buildings. The results of the first campaign suggest a well-planned settlement structure with specialized areas for the production or refinement of copper and copper objects. Of particular importance was the discovery of multiple plano-convex copper ingots during the excavations of one of the domestic buildings.
Keywords: Archéologie – Oman